2012
DOI: 10.1002/joc.3613
|View full text |Cite
|
Sign up to set email alerts
|

Wind speed trends over China: quantifying the magnitude and assessing causality

Abstract: ABSTRACT:Temporal trends in 10-m wind speeds from homogeneous observational data sets from 540 weather stations and reanalysis data sets are quantified and compared. Also, possible physical cause of inconsistencies between the data sets and temporal trends and variability in wind speeds are investigated. Annual mean wind speeds from the observational data exhibit pronounced downward trends especially in the upper percentiles and during spring. The NCEP/NCAR reanalysis reproduces the observed wind speeds, seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 48 publications
(105 reference statements)
10
79
3
1
Order By: Relevance
“…8, the wind speed series after adjustment at all 10 stations were coincident, with a reducing trend at the 95% significant level. This result is consistent with current researches on assessment of observed near-surface wind speed trends in China (Rong and Liang 2008;Cheng 2010;Zou et al 2010;Fu et al 2011;Guo et al 2011;Chen et al 2013;Zhang et al 2014;Xiong 2015), and also similar to trends reported for other parts of the world (Pryor et al 2009;Wan et al 2010;William and Martha 2014). Based on the adjusted data, the trends in the regional average annual and seasonal (spring, summer, autumn, and winter) wind speed series were −0.277, −0.325, −0.228, −0.223, and −0.336 m s −1 /10a, respectively (Fig.…”
Section: Trend Amplitudes Before and After Adjustmentsupporting
confidence: 91%
See 3 more Smart Citations
“…8, the wind speed series after adjustment at all 10 stations were coincident, with a reducing trend at the 95% significant level. This result is consistent with current researches on assessment of observed near-surface wind speed trends in China (Rong and Liang 2008;Cheng 2010;Zou et al 2010;Fu et al 2011;Guo et al 2011;Chen et al 2013;Zhang et al 2014;Xiong 2015), and also similar to trends reported for other parts of the world (Pryor et al 2009;Wan et al 2010;William and Martha 2014). Based on the adjusted data, the trends in the regional average annual and seasonal (spring, summer, autumn, and winter) wind speed series were −0.277, −0.325, −0.228, −0.223, and −0.336 m s −1 /10a, respectively (Fig.…”
Section: Trend Amplitudes Before and After Adjustmentsupporting
confidence: 91%
“…The statistics based on the adjusted data here were generally consistent with those from Li et al (2011), who evaluated the regional trends (Table 4). Both this study and the prior study indicate that the decreasing amplitudes of wind speed trend in spring and winter were much larger than those in summer and autumn; this is also reflected in studies on annual and seasonal wind speed change over China (Xu et al 2006;Jiang et al 2010;Guo et al 2011;Fu et al 2011;and Chen et al 2013). Accordingly, based on the adjusted data, characteristics of near-surface wind speed change in Tianjin are consistent with those of regional background climate in China.…”
Section: Trend Amplitudes Before and After Adjustmentsupporting
confidence: 81%
See 2 more Smart Citations
“…Due to the uncertainty unavoidably associated with future projections, the nodes ProjectedRainfall and ProjectedWindSpeed are described by imprecise random variables. Climate data projections for the north-western region of China have been deduced from the available literature [5] as well as the baseline for the wind speed distribution [1]. Conversely, the probability distribution of rainfall has been defined on the basis of the data collected close to the station of reference.…”
Section: Climate Scenariosmentioning
confidence: 99%